Interaction of the nervous system and vascular system is required for the proper assembly of the neocortex. (October 2019) - Takashima, Satsuki; Watanabe, Chisato; Ema, Masatsugu; Mizutani, Ken-ichi
Abstract: Mammalian neocortical development encompasses an entire set of events that leads to the generation of excitatory and inhibitory neurons from neural progenitors in the dorsal and ventral telencephalon, including cell proliferation, production of migratory precursors and their progeny, differentiation, and integration into circuits. During these processes, the developing neocortex acquires its vasculature by angiogenesis, a process consisting of proliferation of endothelial cells in existing blood vessels or vascular plexuses, and leading to formation of new blood vessels. Recent studies have suggested that neocortical angiogenesis progresses in a spatially and temporally restricted manner to construct a specialized vascular niche that supports ongoing neurogenesis during neocortical development. Here we review that periventricular blood vessels selectively influence neocortical progenitors behavior and neurogenesis, highlighting how CNS angiogenesis is utilized to construct neocortical cytoarchitecture. Highlights: Blood vessels selectively influence neocortical progenitor. Vascular niche influences neural migration and differentiation. CNS angiogenesis is utilized to construct neocortical cytoarchitecture.